GLUT1 and CAIX expression profiles in breast cancer correlate with adverse prognostic factors and MCT1 overexpression - Pinheiro, Céline (2011)
We thank Dr. Vitor Carneiro (pathologist from the Hospital do Divino Espírito Santo, Ponta Delgada, São Miguel, Azores), for his help in retrieving the breast cancer samples for this study.